2023
DOI: 10.30813/bricolage.v9i1.3864
|View full text |Cite
|
Sign up to set email alerts
|

Fragmented self of Gen Z in Instagram: Digital dramaturgy on Bourdieu’s logic of practice

Abstract: <p>This research aims to identify the Self formed by Self-Presentation through different social media channels. This presentation of the Self's process is known as Dramaturgy. This study also identifies the Dramaturgy carried out by this study's participants by considering the Doxa, Habitus, Arena, and Capital surrounding the participants. Frameworks of this research are Goffman's Presentation of Self and Dramaturgy; and Bourdieu's Logic of Practice. This research relies on the constructivism paradigm, u… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
0
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 0 publications
1
0
0
Order By: Relevance
“…These finding are consistent with the study of Herawati et al (2022), which found that social media application are inseparable part of Generation Z life. The findings are also consistent with the study of Agustin & Angeliqa (2023), which revealed that Instagram is the most utilised social media application by Generation Z. Question No.…”
Section: Section Two: Analysing Digital Characteristics Of Generation...supporting
confidence: 88%
“…These finding are consistent with the study of Herawati et al (2022), which found that social media application are inseparable part of Generation Z life. The findings are also consistent with the study of Agustin & Angeliqa (2023), which revealed that Instagram is the most utilised social media application by Generation Z. Question No.…”
Section: Section Two: Analysing Digital Characteristics Of Generation...supporting
confidence: 88%